Prospects of using information technologies and artificial intelligence in the process of teaching the subject of anatomy-physiology - Azikuri, Gela (International Scientific Conference “EDUCATION, RESEARCH, PRACTICE” Proceedings, 2024)
As a result of the research, it was determined that modern technologies increase the quality of students' education, using high technologies of virtual reality reduces the duration of information transfer, improves and modernizes the laboratory and practical work process of students. Lecturers and students are given the opportunity to receive information and work through spatial, interactive, models of human anatomy, which makes the learning process more interesting and fun. The use of artificial intelligence resources such as ChatGpt, Gemini, Microsoft Copilot, Heuristi.ca, OpenReead, acefy.ai, AdobeFirefly and Ideogram allow students to consolidate knowledge and facilitate preparation in such components of learning as working on open and closed tests, creating quizzes and cases, to organize an interesting discussion-debate, to better prepare for midterm and final exams, to gain solid knowledge.